2003
DOI: 10.1021/bi034653e
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of AMP-Bound PDE4 Suggests a Mechanism for Phosphodiesterase Catalysis,

Abstract: Cyclic nucleotide phosphodiesterases (PDEs) regulate the intracellular concentrations of cyclic 3',5'-adenosine and guanosine monophosphates (cAMP and cGMP, respectively) by hydrolyzing them to AMP and GMP, respectively. Family-selective inhibitors of PDEs have been studied for treatment of various human diseases. However, the catalytic mechanism of cyclic nucleotide hydrolysis by PDEs has remained unclear. We determined the crystal structure of the human PDE4D2 catalytic domain in complex with AMP at 2.4 A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 47 publications
6
145
0
1
Order By: Relevance
“…On the other hand, recent study on the PDE4-AMP structure showed that the metal also interacts with the phosphate oxygen and thus strongly suggests a catalytic role. 10 The strong anomalous scattering at the wavelength of the zinc absorption edge suggests the first metal is a zinc, and is consistent with the fact that zinc, at low concentration, activates the enzyme. 9 In PDE4D2, the second metal ion coordinates with D318, a bound water, and possibly with the phosphate group of the substrate.…”
Section: Introductionsupporting
confidence: 63%
“…On the other hand, recent study on the PDE4-AMP structure showed that the metal also interacts with the phosphate oxygen and thus strongly suggests a catalytic role. 10 The strong anomalous scattering at the wavelength of the zinc absorption edge suggests the first metal is a zinc, and is consistent with the fact that zinc, at low concentration, activates the enzyme. 9 In PDE4D2, the second metal ion coordinates with D318, a bound water, and possibly with the phosphate group of the substrate.…”
Section: Introductionsupporting
confidence: 63%
“…The superposition of PDE4D2-cAMP over PDE4D-AMP and PDE4B-AMP (18,21,28) yielded the small RMSDs of 0.26-0.73 Å, indicating overall similarity of the structures. In addition, the structural comparison shows some features shared by AMP and cAMP.…”
Section: Product Amp Does Not Simulate Binding Of Substrate Campmentioning
confidence: 95%
“…The cDNA for expression of the catalytic domain of the wild type PDE4D2 was purchased from ATCC (American Type Culture Collection, ATCC #5654749) and subcloned into pET15b, as described previously (21). The plasmid pET-PDE4D for expression of the wild type PDE4D2 (residues 86-413) was mutated to pET-D201N with the QuickChange sitedirected mutagenesis kit (Stratagene) using the PCR primers of 5′-GCCAGTGCAATACATAATGTAGATCATCCTGG-3′ and 5′-CCAGGATGATCTACATTATGTATTGCACTGGC-3′.…”
Section: Protein Expression Crystallization and Structure Determinationmentioning
confidence: 99%
See 2 more Smart Citations